Library information systems : - Kochtanek, Thomas R (Libraries Unlimited, 2002)
This volume provides an overview of the history of library information systems, underlying technologies, design and types of systems, standards, the implementation process, management, and a few predictions. Chapter 8, "Basic Technology Axioms," is both a good teaching platform and a reminder to those who long for the "good old days" that the potentially "good new days" are here to stay. The glossary and definitions throughout the work provide a good core for learning to speak modern "libraryese." Many chapters have suggested bibliographies of Web and print resources